AFFECTIVE PUBLICS: “MAY GOD BLESS YOUTUBE” - Bagdogan, Seyda (AoIR Selected Papers of Internet Research, 2023)
This paper is about Turkish women cooking on YouTube and how their digital labour is connected to the feminization of work in global aspect through affective publics next to hope labour and care delivery. Papacharissi (2015) explains affective publics as “publics that have been transformed by networked technologies to suggest both spaces for the interaction of people, technology, and practices and the imagined collective that evolves out of this interaction” (pp:125-126). Since offline and online activities are entwined in everyday life due to a great amount of interaction, the networked performance of self emerges along with digital steps an individual takes (Papacharissi, 2015: p.99). When a person makes a move online, (s)he performs towards an [imagined] audience that is shaped by her/his background and daily life. Because identity within presentation and narrative is performative and requires reflexivity in intra-publics as Papacharissi states (2010): “The sense of self-sustained is reflexively adjusted across platforms, publics, and taste cultures to enable optimal expression and connection. The management of this reflexivity, across spaces, publicly private and privately publicly, generates both tension and opportunity for the individual”. From the point of a networked self, gender and religion play a significant role since they are subtly embedded into manners and visibly marked in bodies, in particular, in Islam. While Muslim women blossom on social media as an influencer through consumer culture, they keep modest dressings and use their profile to be inspirational by supporting their acts on their faith base (Waltorp, 2015; Kavakci, & Kraeplin, 2017).